2022
DOI: 10.1007/s00449-021-02674-9
|View full text |Cite
|
Sign up to set email alerts
|

Automatic system for high-throughput and high-sensitivity diagnosis of SARS-CoV-2

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had severe consequences for health and the global economy. To control the transmission, there is an urgent demand for early diagnosis and treatment in the general population. In the present study, an automatic system for SARS-CoV-2 diagnosis is designed and built to deliver high specification, high sensitivity, and high throughput with minimal workforce involvement. The system, set up wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…The evaluated results show that both techniques have adequate and equivalent values of sensitivity (RT-LAMP: 82.8%, CPA: 83%) and specificity (RT-LAMP and CPA: 91.5%), as well as a high concordance (88%) between both techniques. Our results are in line with previous studies such as that of Lu et al [5] showed that the CPA technique shows high sensitivity and specificity versus the gold standard, been able to detect from 100 copies of ARN per reaction tube. On the other hand, Rai et al [16] based on a systematic review of different molecular techniques for SARS-CoV-2 detection found that RT-LAMP is capable to detect from 4 copies/uL.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The evaluated results show that both techniques have adequate and equivalent values of sensitivity (RT-LAMP: 82.8%, CPA: 83%) and specificity (RT-LAMP and CPA: 91.5%), as well as a high concordance (88%) between both techniques. Our results are in line with previous studies such as that of Lu et al [5] showed that the CPA technique shows high sensitivity and specificity versus the gold standard, been able to detect from 100 copies of ARN per reaction tube. On the other hand, Rai et al [16] based on a systematic review of different molecular techniques for SARS-CoV-2 detection found that RT-LAMP is capable to detect from 4 copies/uL.…”
Section: Discussionsupporting
confidence: 93%
“…The importance of applying molecular screens is that they can detect the presence of virus or its remnants [5] at any stage of the disease, because these screens have been shown to detect high, medium and low viral loads, unlike serological tests because performance is influenced by symptomatology, days of infection, or virus lineage and they are not confirmatory tests for the disease [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,[30][31][32] In the realm of molecular diagnostics, a sensitivity of 100 copies is considered quite good for many applications. [33][34][35] For highly sensitive diagnostic tests such as the detection of trace amounts of pathogens, even greater sensitivity might be necessary to detect lower quantities of targets, such as singledigit or even single-copy detection. 36 To improve the sensitivity of the PCR/SERS assay for DNA targets, the following two factors should be considered: (i) optimization of the PCR amplification, including the primer design, PCR thermal cycle conditions, PCR buffer and components; and (ii) optimization of the SERS-active substrates that could enhance the Raman signal intensities.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…The system involves 6 main steps, and 6 different equipment are needed to complete each step. Another automatic system having better compactness (one single floor-type equipment) and higher throughput has been proposed that can carry out SARS-CoV-2 detection of 192 samples under 180 min at detection limit of 100 copies per reaction ( Lu et al, 2022 ). In this work, we propose a desktop type automatic detection system that can detect SARS-CoV-2 of 384 samples in around 30 min with detection limit of 100 TCID 50 /ml.…”
Section: Introductionmentioning
confidence: 99%